The determinants of online buying intention - Junita Safitri; Paham Ginting; Endang Sulistya Rini; Arlina Nurbaity Lubis (Proceedings of AICS - Social Sciences, 2017)
Today Social Media is something that you cannot live without. Most of us today addicted to Social Media. Social Media had changed many things in our life. We are communicating, chatting, sharing, inspiring and shopping simultaneously using Social Media. Despite offering so much fun, social Media can be very dangerous. In Aceh Province online shoppers prefer Social Media to Online website for online shopping option. This study is a quantitative research which tested the role of two beliefs of technology usage perceived ease of use and perceived usefulness as determinant factor along with social influence in influencing online buying intention. Purpose of this study is to identify the affecting factor of social media buying intention. The population of this study was Social Media User who experience online shopping and located in Aceh. This study was conducted using 199 respondents as samples which were taken from specific population. This study were using Observation and Questionnaires as data collecting method. Partial Least Square (PLS) used as data analyzing method. This study resulted that online buying intention significant in influencing online buying behavior. Perceived Usefulness is significant in influencing online buying intention. Social Influence found significant in influencing online buying intention.